Análise do processo de transformação digital de uma empresa de manufatura localizada no Brasil: estudo de caso único - Corrêa, Gustavo Felipe Mendes; Zalla, Giovanna Dias (Universidade Federal de São Carlos, 2020)
The advancement of new digital technologies has driven organizations to adapt their strategies and businesses. In this scenario, the present study aimed to verify how a company located in Brazil has adapted its business to the process of digital transformation. To this end, a qualitative research approach was used, and a case study was conducted with a large manufacturing company. The data were collected through interviews, documents, and direct observation. The data analysis allowed to verify: (a) a clear need for transition and changes for industry 4.0 due to the market demand; (b) evidence of the implementation and adoption of technologies such as internet of things, cloud computing, artificial intelligence, and data mining; (c) practices and changes in the organizational environment resulting from digital transformation, such as the creation of new areas dedicated to digital transformation, stimulating innovation and open communication, holding workshops, events, training, collaboration with external partners and benchmarking; and (d), finally, the existence of barriers as financial, knowledge of technologies, support from leadership and organizational culture. At this point, it was found that the necessary change for digital transformation in companies goes far beyond technological issues or new work tools. The basis for transforming processes, actions, and operating mode is mainly in the mindset of employees and leadership. This work brings theoretical contributions, by approaching a topic that is still little explored in the Brazilian context and adding evidence to the literature, and managerial ones for providing insights and clarifying practices to managers.
Analysis of the process of digital transformation in a manufacturing company located in Brazil: a single case study
Keywords: Indústria 4.0; Tecnologias digitais; Transformação digital; Estudo de caso; País emergente; Industry 4.0; Digital technologies; Digital transformation; Case study; Emergent country; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS::ADMINISTRACAO DA PRODUCAO; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS